1999
DOI: 10.1007/s002640050299
|View full text |Cite
|
Sign up to set email alerts
|

Infected total hip arthroplasty - the value of intraoperative histology

Abstract: Intraoperative histology showed a sensitivity of 100% and a specificity of 98%. These results were better than those observed for the other tests evaluated. Our data provide evidence that intraoperative histology is useful tool in the diagnosis of infected total hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
1
12
0
3
Order By: Relevance
“…1, 4 The present study and the more recently published articles 8,[10][11][12] that used as gold standard of infection the presence of microorganisms in periprosthetic tissue coincide about the lower values of sensitivity ( Table 3). The problem is the pathogenic significance of intraoperative cultures in the absence of clinical symptoms and inflammatory signs in periprosthetic tissue.…”
Section: Discussionmentioning
confidence: 91%
“…1, 4 The present study and the more recently published articles 8,[10][11][12] that used as gold standard of infection the presence of microorganisms in periprosthetic tissue coincide about the lower values of sensitivity ( Table 3). The problem is the pathogenic significance of intraoperative cultures in the absence of clinical symptoms and inflammatory signs in periprosthetic tissue.…”
Section: Discussionmentioning
confidence: 91%
“…4 Reviewing the literature (Table 4), there is a lot of variability in the specimen submitted for histological evaluation. Some investigators did not obtain interface membrane 5,18,33,34 and others did not define the type of specimen analyzed. 10,13,21 It is generally accepted that there is no important differences between tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures and polymorphonuclear leukocytes count from periprosthetic tissue are the gold standard for the diagnosis of prosthetic joint infections. 2 The specificity and sensitivity of histology has never been 100% [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and this may be for different reasons. 5,12,22,23 False-positive results of histology could be because culture and histological specimens are taken from different areas.…”
mentioning
confidence: 99%
“…Labeled leukocyte imaging studies, including both Technetium-99 (Tc-99) [ 26 , 72 , 75 , 78 ] and Indium-111 (In-111) scans [ 26 , 33 , 48 , 64 , 68 ], have demonstrated value in diagnosis of infection; among these studies, In-111 demonstrated more effectiveness as a "rule out" test. Furthermore, several studies examined a combination of Tc-99 bone scans with either Tc-99 [ 65 ] or In-111 white blood cell (WBC) scans [ 33 , 73 , 79 ], which improved the overall diagnostic value. Likewise, labeled leukocyte imaging combined with bone marrow imaging demonstrated effectiveness in diagnosis of PJI [ 34 , 46 , 51 , 75 ].…”
Section: Imagingmentioning
confidence: 99%